The Sensitivity of Temperature to Tachyhydrite Formation: Evidence from Evaporation Experiments of Simulated Brines Based on Compositions of Fluid Inclusions in Halite. (3rd July 2019) - Cheng, Huaide; Hai, Qingyu; Li, Jun; Song, Jianguo; Ma, Xuehai
Abstract : An average of concentrations of Na +, Mg 2+, Ca 2+, K +, and Cl – in fluid inclusions, from the Khorat Plateau evaporite primary halite, was employed. The evaporation–crystallization sequence and paths were obtained under various temperature conditions for the quinary system, Na +, K +, Mg 2+, Ca 2+ //Cl – -H2 O. The results showed (1) a halite, sylvite, and carnallite stage at 25°C; (2) a halite, sylvite, carnallite, and bischofite stage at 35°C; and (3) a halite, sylvite, carnallite, bischofite, and tachyhydrite stage at 50°C. These results indicated that (1) a hot state is favorable for tachyhydrite formation, (2) tachyhydrite occurs in the late evaporation stage, and (3) the stability field of tachyhydrite increases with increasing temperature. The crystallization paths were plotted by the application of Jänecke phase diagram at 25°C, 35°C, and 50°C involving the system Na +, K +, Mg 2+, Ca 2+ //Cl – -H2 O. The crystallization sequence predicted on the Jänecke phase diagram showed a good agreement with the experimental crystallization sequences and paths. Tachyhydrite precipitate more easily from a high Ca concentration solution during the late evaporation stage with increasing temperature under the same relative humidity condition. The evaporite mineral succession in the Khorat Plateau, Sergipe, and Congo basins agrees well with the mineral precipitation sequences predicted from their own fluid inclusions in halite. This is confirmed by the simulation of the Jänecke phase diagram at 50°C involving the system Na +, K +, Mg 2+, Ca 2+ //Cl – -H2 O. The precipitation of tachyhydrite was sensitive to the temperature, and that the thermal resource may originate from a temperature profile in the solar pond. This study presented a simulated approach that can help in understanding similar cases that studies the sensitivity of temperature to salt formation.